TREND PENELITIAN AKUNTANSI SYARIAH DI INDONESIA - ACHMAD RYZKY; RINI RINI (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2018)
The purpose of this research is to explain the development of sharia accounting research. This study uses content analysis methods on the number of published papers, author institutions, and research areas within the topic of Islamic accounting. The sample used amounted to 1404 papers published in journals that were published in the national accounting symposium proceedings during 2008 – 2017. The result of the research shows that there is no consistent improvement to the contribution of sharia accounting papers. In addition, most of the authors of sharia accounting papers are from public universities, and the most popular research area is the topic of sharia banking.